Mindfulness-Based Counseling Techniques for Stress Management: Improving Self-Efficacy Among High School Students - Zainatus Salma Al Qolbi (P3M STAI Kuningan, 2025)
Background: High school students face increasing levels of academic stress, peer pressure, and future-related anxiety, which negatively impact their mental health and self-efficacy. Understanding effective interventions to address these psychological challenges is critical for supporting adolescent development and academic performance.Objective: This study examines the effectiveness of mindfulness-based counseling techniques in managing stress and improving self-efficacy among high school students.Method: Using a quasi-experimental design with a pretest-posttest control group, this research involved 120 students aged 15-17 years from two public high schools. The experimental group received eight weekly sessions of mindfulness-based counseling interventions, including breathing exercises, body scan meditation, mindful awareness practices, and cognitive restructuring techniques. Data were collected using the Perceived Stress Scale (PSS), General Self-Efficacy Scale (GSES), and Mindful Attention Awareness Scale (MAAS).Findings and Implications: Results revealed significant improvements in the experimental group compared to the control group, with decreased stress levels and increased self-efficacy scores. The intervention also enhanced students' emotional regulation, attention focus, and coping mechanisms. These findings suggest that mindfulness-based counseling techniques offer practical and effective tools for school counselors to address adolescent stress and promote psychological resilience.Conclusion: Mindfulness-based counseling interventions demonstrate significant effectiveness in reducing stress and enhancing self-efficacy among high school students, providing evidence-based strategies for school-based mental health support programs.